Influencer Marketing and Its Effectiveness in Shaping Consumer Purchase Intentions - Tirta Mulyadi; Eko Wahyu Widayat; Siti Nurhayati (Yayasan Riset dan Pengembangan Intelektual, 2025)
Influencer marketing has become one of the most powerful strategies in the digital era for shaping consumer purchase intentions. This article review examines studies published between 2020 and 2025 to explore how influencers affect consumer attitudes, brand perceptions, and purchasing decisions. The review identifies three core drivers of effectiveness: the credibility and authenticity of influencers, the depth of consumer engagement on social media platforms, and the mediating role of brand trust, loyalty, and emotional connection. It also highlights the growing importance of value-driven strategies such as ethical and sustainable marketing in strengthening positive purchase intentions. Moreover, the integration of influencer strategies with interactive tools such as live commerce, affiliate marketing, and content variety-seeking behaviors has shown significant potential in enhancing consumer responses. The findings emphasize the need for brands to align influencer selection and campaign design with evolving consumer expectations. The review concludes that influencer marketing is highly effective in shaping purchasing decisions but calls for further longitudinal and cross-cultural research to understand its long-term impacts and sustainability.